Antecedents of Cloud Computing Adoption in the Malaysian context: A Systematic Literature Review - Teh, Raymond; Subramaniam, Anusuiya; Ho, Jo Ann; Kamal Basha, Norazlyn (Journal of Technology Management and Business, 2021)
In a competitive marketplace, the competitiveness and survival of any corporation are often attributed to its ability to adopt innovative technology which bestows a competitive edge and reduced costs, improves the quality and the efficiency of its business processes. Cloud computing is a platform for the development of computational solutions for multiple fields of knowledge, as it offers cost-saving mechanisms and increased efficiency to organisations. Despite its maturity and enhancement, reviews pertaining to antecedents of cloud computing adoption in the Malaysian context are scarce. Thus, a systematic literature review using Scopus database for retrieving the related articles was carried out to shed light on the antecedents of cloud computing adoption in the Malaysian context. The review revealed that the antecedents influencing cloud computing adoption include technological context elements (relative advantages, technological readiness, cost-saving, and compatibility), organisational context elements (top management support), and environmental context elements (competitive pressure, external support/trading partner support/regulatory support, vendor reputation and trust). Understanding the antecedents of cloud computing adoption is crucial towards strengthening cloud computing adoption and, in turn, will improve the performance and competitiveness of corporate sectors.